2004
DOI: 10.1038/ncb1209
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of EGFR signalling through integrin-α1β1-mediated activation of protein tyrosine phosphatase TCPTP

Abstract: Integrin-mediated cell adhesion regulates a multitude of cellular responses, including proliferation, survival and cross-talk between different cellular signalling pathways. So far, integrins have been mainly shown to convey permissive signals enabling anchorage-dependent receptor tyrosine kinase signalling. Here we show that a collagen-binding integrin alpha(1)beta(1) functions as a negative regulator of epidermal growth factor receptor (EGFR) signalling through the activation of a protein tyrosine phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
164
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 29 publications
11
164
0
1
Order By: Relevance
“…Integrin b1-mediated cell adhesion regulates a multitude of cellular responses, including proliferation, survival and cross-talk between different cellular signaling pathways. A collagen-binding integrin a1b1 functions as a negative regulator of epidermal growth factor receptor (EGFR) signaling through the activation of a protein tyrosine phosphatase [22,23]. Integrinmediated cell-ECM interactions play a critical role in cell adhesion, migration and morphogenesis during vertebrate retinal development [24].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin b1-mediated cell adhesion regulates a multitude of cellular responses, including proliferation, survival and cross-talk between different cellular signaling pathways. A collagen-binding integrin a1b1 functions as a negative regulator of epidermal growth factor receptor (EGFR) signaling through the activation of a protein tyrosine phosphatase [22,23]. Integrinmediated cell-ECM interactions play a critical role in cell adhesion, migration and morphogenesis during vertebrate retinal development [24].…”
Section: Discussionmentioning
confidence: 99%
“…It is the charged chemical nature of spermidine that is thought to play a critical role in the biological activity of the compound, including its activating effect on various enzymes like TCPTP (14,24,25). Although the proposed mechanism by which spermidine increases TCPTP activity has not been clearly defined, it is known that spermidine interacts with TCPTP at the same site as the ␣ 1 -integrin cytoplasmic tail residues 1164 -1179 identified previously to activate TCPTP (6,14). One current hypothesis suggests that the polycationic character of spermidine is responsible for breaking an autoregulatory intramolecular bond between the carboxy-terminal and catalytic domain in TCPTP (14).…”
Section: Discussionmentioning
confidence: 99%
“…PTPs play an integral role in regulating a variety of basic cellular processes, including cell growth and differentiation (5). Among TCPTP substrates are the phosphotyrosine residues on the receptors for epidermal growth factor (6) and insulin (7). Additionally, TCPTP negatively regulates phosphorylation of the IFN-␥ receptor (IFN␥R) and the IFN-␥ signaling molecules signal transducers and activators of transcription (STAT) 1 and 3 (8, 9).…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Activation of Rac1 can be mediated by multiple mechanisms, including activation of tyrosine kinase receptors, such as the EGFR (38,51). It has been shown that loss of integrin ␣1␤1 leads to upregulated EGFR tyrosine phosphorylation (39). In addition, ROS can initiate a number of physiological responses, including tyrosine phosphorylation of growth factor receptors, such as platelet-derived growth factor receptor and EGFR (23).…”
Section: Fig 7 Ros Partially Contribute To Increased Egfr Phosphorymentioning
confidence: 99%